Volume 2: Combustion, Fuels and Emissions, Parts a and B 2010
DOI: 10.1115/gt2010-22286
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a Multiple-Injection Burner to Dry Low-NOx Combustion of Hydrogen-Rich Fuels

Abstract: To demonstrate the applicability of a “multiple-injection burner” to dry low-NOx combustion of hydrogen-rich fuels, the combustion characteristics of a burner were experimentally investigated. The experimental results show that a burner with a flame lift-off length of 5 mm and a fuel-injection-hole diameter of 1.5 mm achieves low NOx concentration of less than 6 ppm for hydrogen-rich fuels with a wide range of hydrogen concentrations. This finding demonstrates that the burner achieves dry low-NOx combustion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A heat recovery steam generator (HRSG) produces steam using the waste heat of exhaust gas from the gas turbine, and sends the steam to the gasifier in order to produce the raw syngas and to a steam turbine in order to generate additional power. The gas turbine combustors are required to operate on oil fuel as the startup fuel at ignition and during part load in order to provide the HRSG with the waste heat until the syngas fuel is supplied to the gas turbine [3].…”
Section: Ccs-equipped Oxygen-blown Igcc Technology and Technical Hurd...mentioning
confidence: 99%
See 1 more Smart Citation
“…A heat recovery steam generator (HRSG) produces steam using the waste heat of exhaust gas from the gas turbine, and sends the steam to the gasifier in order to produce the raw syngas and to a steam turbine in order to generate additional power. The gas turbine combustors are required to operate on oil fuel as the startup fuel at ignition and during part load in order to provide the HRSG with the waste heat until the syngas fuel is supplied to the gas turbine [3].…”
Section: Ccs-equipped Oxygen-blown Igcc Technology and Technical Hurd...mentioning
confidence: 99%
“…Step 1 evaluates performance of single burners in terms of emissions of NOx, CO, and unburned hydrocarbons (UHC), and stability, which is related to pressure fluctuations due to combustion oscillation. The single-burner combustion test showed that the operating range of stable low NOx combustion was restricted by the occurrence of combustion oscillation, and it was probably triggered by the attachment of the flame to the perforated plate due to the ignition of flammable mixtures in the wake behind the plate [3]. In order to suppress the combustion oscillation, a convex burner was suggested.…”
Section: Combustor Development 41 Development Approachmentioning
confidence: 99%
“…These injectors are similar to LDI, but include a small premixing zone, and may approach the operability characteristics of LDI if designed carefully. Configurations in the literature include jet-in-crossflow mixing [8], coflow mixing in channels [9], and swirl-based mixing in small "cups" with radial and axial inflow [10]. The latter concept was incorporated into a 1.3 MW fuel injector array that was built with a macrolamination process and operated at pressures of 8 to 12 bar with fuels consisting of hydrogen, natural gas, nitrogen and/or carbon dioxide [11].…”
Section: Introductionmentioning
confidence: 99%
“…The successful introduction of CCS into IGCC plants requires advanced technologies for diluent-free ("dry"), low-NOx combustion of hydrogen-rich syngas fuels that are capable of achieving both lower NOx emissions and higher plant efficiency. The authors have been developing a "multiple-injection burner" as an advanced concept for hydrogen-rich fuels (Asai, et al, 2010(Asai, et al, , 2011. This burner consists of multiple fuel nozzles and a perforated plate with multiple air holes.…”
Section: Introductionmentioning
confidence: 99%